Hydrothermal synthesis and characterization of visible-light-driven Cl-doped Bi2WO6nanoplate photocatalyst - Anukorn Phuruangrat (2018)
© 2017 The Ceramic Society of Japan. All rights reserved. Pure Bi2WO6and Cl-doped Bi2WO6nanoplates were successfully synthesized by hydrothermal method. The characteristic results revealed the presence of orthorhombic Bi2WO6products with 200300nm square-like nanoplates and anionic Cl incorporated in the Bi2WO6lattice. In this research, the photocatalytic activity of Cl-doped Bi2WO6nanoplates was tested through the degradation of Rhodamine B under visible light irradiation. The 3wt% Cl-doped Bi2WO6exhibited higher photocatalytic activity for degradation of Rhodamine B than other Bi2WO6photocatalysts.